Development of a microcontroller based automobile speed limiting device and alarm control system - Oluwaseun Ibrahim Adebisi; Isaiah Adediji Adejumobi; Folasade Olayinka Durodola; Haastrup Ayobami Jim (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Road accident due to overspeeding is a common occurrence in a developing nation such as Nigeria. Therefore, the need for a device capable of notifying a vehicle driver when the allowed speed limit of an area is exceeded arises. In this work, a microcontroller based automobile speed limiting device and alarm control system was designed and developed. The core components employed for the system design include Arduino Nano microcontroller, 1602 liquid crystal displays (LCD) module, light-emitting diodes (LEDs), buzzer, 18650 battery, I2C, infrared detectors and push buttons. Data gathering and circuit designs were implemented with microcontroller as focal point using suitable design models. Performance test was carried out on the developed system and the device’s reading error was determined. The developed automobile speed limiting device and alarm control system was functional and performed satisfactorily during testing. The reading error of the device was evaluated as 5.83%. The developed speed limiting device, apart from being suitable and efficient for vehicle speed measurement, could also be deployed for general applications requiring speed measurement.